1996
DOI: 10.1007/bf02116836
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of posttraumatic symptomatology by relaxation and visual-kinesthetic dissociation

Abstract: Five patients suffering from posttraumatic stress disorder and experiencing persistent intrusive imagery were treated with two sessions of relaxation training followed by two sessions of the visual-kinesthetic dissociation technique. Outcome was monitored using a multiple baseline design. Despite the briefness of the intervention, three of the patients showed an almost complete reduction in the frequency of their intrusive images and substantial changes on other measures of psychopathology. One patient showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Here, an argument for a mechanism based on the emerging evidence for memory reconsolidation has been presented that is congruent with the structural elements of the intervention and predicts similar results (Dietrich, 2000;Hossack & Bentall, 1996;Koziey & McLeod, 1987;McDowell & McDowell, n.d.).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Here, an argument for a mechanism based on the emerging evidence for memory reconsolidation has been presented that is congruent with the structural elements of the intervention and predicts similar results (Dietrich, 2000;Hossack & Bentall, 1996;Koziey & McLeod, 1987;McDowell & McDowell, n.d.).…”
Section: Discussionmentioning
confidence: 57%
“…Figley reviews the technique and provides a case study. Each of the referenced studies recommends the technique as a valuable tool for treating PTSD and makes suggestions for further research (Carbonell & Figley, 1999;Dietrich et al, 2000;Figley, 2002;Hossack & Bentall, 1996;Koziey & McLeod, 1987;Muss, 1991Muss, , 2002. There is also one non-peer-reviewed study that is reported online (Guy & Guy, 2003).…”
Section: Reconsolidation and The Visual-kinesthetic Dissociation Protmentioning
confidence: 99%
“…The visual kinaesthetic dissociation procedure is essentially an information-processing technique that has proven successful in resolving individual cases of physical and sexual abuse, including rape (Hossack & Bentall, 1996;Kosiey & Mcleod, 1987). Horowitz (1976a, b) proposed that in nontraumatic situations information is assimilated into existing cognitive schema, the defensive functioning regulating the information processing.…”
Section: Trauma Processingmentioning
confidence: 99%
“…Effect sizes using Hedge's unbiased g statistic are calculated for the groups and are reported in table 2. Visual-Kinesthetic Disassociation (V/KD) (Bandler & Grinder, 1979) facilitates the attainment of a degree of kinesthetic dissociation as the individuals visually reexperience their trauma (Hossack & Bentall, 1996), enabling them to process the event( s) from a de-centered perspective. The approach has not been researched with persons with complex posttraumatic and dissociative disorders, and should be utilized with care with this clientele in the absence of further study, since it facilitates dissociation.…”
Section: Traumatic Incident Reduction (Tir)mentioning
confidence: 99%